Designing Collaborative Project-Based Learning (CR-PjBL) with AI Media to Enhance Students’ Critical Thinking Skills - Nor Soleh; Muhtarom; Lukman Harun (Jurnal Inovasi Matematika, 2026)
The main problem in this study is that many students find mathematics difficult, and their critical thinking skills in mathematics remain low. The objectives of this study are to analyze the difficulties in learning mathematics, particularly critical thinking skills, identify various alternative solutions that can be used to enhance students' critical thinking abilities, and develop a prototype based on solutions aligned with the design thinking approach, tailored to the needs of both students and teachers, advancements in science and technology, and the demands of the curriculum in the Society 5.0 era. This study uses a design thinking approach with five stages: empathize, define, ideate, prototype, and test. The population in this study consists of seventh-grade students and mathematics teachers from five public schools in Semarang Regency, totaling 534 students and 12 mathematics teachers, reinforced with meta-analysis techniques adapted to the ideas from the ideate phase that emerged. The findings of this study indicate innovative learning solutions to enhance middle school students' critical thinking skills as follows: (1) Designing CR-PjBL learning using Canva AI media; (2) Designing CR-PjBL learning using Quizizz media; (3) Developing interactive media based on a website using Canva AI. The application of the design thinking method in developing effective learning models and interactive media can significantly enhance students' critical thinking skills.